Исследование спектра высокого разрешения полосы 2N3 молекулы 32S18O2; Известия вузов. Физика; Т. 60, № 1 - Замотаева В. А. Валерия Александровна; Аслаповская Ю. С. Юлия Сергеевна; Васильев К. С. Кирилл Сергеевич; Федотов Л. Е. Леонид Евгеньевич; Бехтерева Е. С. Елена Сергеевна; Зятькова А. Г. Анастасия Георгиевна (2017, 2017)
Заглавие с экрана